Research in public communication of science and knowledge social appropriation: a decade-long bibliometric study - Marianela Dávila Lorenzo; Angélica Mendieta Ramírez; Josías Hernández Pérez (Medisur)
Foundation: public communication of science has a fundamental role in bridging the knowledge gap between scientists and the public, in order to strengthen the decision-making power of society in the global change crisis. However, the challenges related to the democratization of knowledge and the critical rationality of public discourse, from the level of academic research, are marked. Objective: analyze research production on public communication of science and the social appropriation of knowledge in order to characterize the indicators of scientific productivity and knowledge structure. Methods: a predominantly quantitative descriptive bibliometric approach is assumed, in which 1280 records that make up the sample are processed in the Web of Science and Scopus databases. The following were analyzed: productivity of articles per year, author productivity, collaboration in authorship, geographical distribution, institutional affiliation and productivity of articles by journals, as well as knowledge structure: conceptual structure and social structure. Results: the highest levels of relevance in the knowledge domain are in 2021 represented by countries such as the United States and the United Kingdom with 54.86% of the research in the range. The academic works focus on thematic areas such as: science and media, public understanding of science, technology, health and COVID 19. Conclusions: the intellectual structure warns that public communication of science is consolidated as an interdisciplinary knowledge area , although there is insufficient epistemological legitimacy and reflections with a broad disciplinary tendency in the theoretical proposals of the field.